THE EFFECTS OF BREED AND AGE ON THE CHANGES IN WEIGHT DURING AND AFTER GESTATION IN NATIVE IRAQI SHEEP - F. Aljalili, Z.; M. Hassoon, T. (The Iraqi Journal of Veterinary Medicine, 1988)
Ninety seven Iraqi ewes representing the three major Iraqi breeds (Karadi, Awassi, and Arabi) were used to study the effects of breed and age on the rhythm of weight parameter and its components during gestation. Body weight of ewes was recorded monthly throughout gestation weekly during the suckling period. The weights of newborns were also recorded immediately after birth. The ewes were kept in semi-closed barn and had free access to green food plus a daily allowance of concentrates (0.5Kg). The results indicated the dominance of the Karadi over the Awassi and Arabi in weights during the entire experimental period. The gain in weight for the three breeds averaged 9.0, 9.1, and 8.6 Kg, and constituted 19.6, 21.6, and 22.5% of weights at time of service respectively. Of the total gain, the newborn, fetal membranes and fluids, and net gain constituted 47.64, 39.55, and 12.81% respectively. However, the Arabi in general performed better since it used the weight gained more efficiently. The weights of fetal membranes and fluids were affected by breed but not by age of ewes. On the other hand, younger ewes had higher weight gains during pregnancy than older ones.